Answers

2015-11-11T22:30:58+05:30

This Is a Certified Answer

×
Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.
Let present age of old member = x
let present age of new member = y
need to find (x-y)
let sum of present age of rest members = a

Since present average of 10 members are same as it was 4 years earlier,
y+a = (x-4)+(a-9*4)
⇒ y + a = x + a - 40
⇒ x+a -40 = y+a
⇒ x - y = 40

The new member is 40 years younger than the old member
1 5 1